Degree of Probability of Medical Diagnosis Based on a Case of Child Abuse - Gunathilake, K.M.T.B.; Vidanapathirana, M. (Proceedings of CFPSL 15th Annual Academic Sessions 2016/17, 2016)
Attached

INTRODUCTION Wrong diagnosis of child sexual abuse may lead to serious punishments or complete acquittal of the perpetrator and secondary victimization of the child. This case highlights the importance of meticulous medico-legal investigations to exclude the differential diagnosis before arriving at medico-legal conclusions in order to prevent serious social and medico-legal implications. CASE REPORT An 8 year old girl with genital ulceration disease (GUD) was transferred to a gynecology unit of provincial general hospital. The Venereologist examined the child, and based on the clinical picture the diagnosis was confirmed as “Genital herpes” and antiviral drug treatment was started. However, the swab culture performed by the dermatologist was negative for herpes simplex virus. ; Since this condition is highly suggestive of sexual abuse, the child was referred to Judicial Medical Officer (JMO) for medicolegal investigations. Child and the guardian refused any form of sexual abuse and they related the condition to a leech bite. Mother was abroad and father works in Colombo and comes home every two weeks. On examination, the child had fever, myalgia and tender inguinal lymphadenopathy. Vulva was red and swollen with watery blisters and superficial scars. The hymen was intact. JMO referred the scrapings of the lesions to the Histopathologist. Histopathology showed uniformly stained fibrinous material and infection of virus was unlikely. Samples for HSV antibody tests for both type -1 and 2 IgG arid IgM antibody tests were also negative. Alleged child sexual abuse was excluded. CONCLUSIONS Degree of probability of ascertaining the diagnosis may be different in clinical practice and medicolegal cases. In genital ulceration disease, probable clinical diagnosis is sufficient for medical management but for medico-legal management, the diagnosis should be beyond - j reasonable doubt in order to achieve justice as well us to prevent secondary victimization.